From Diabetes Care to Diabetes Cure—The Integration of Systems Biology, eHealth, and Behavioral Change - van Ommen, Ben; Wopereis, Suzan; van Empelen, Pepijn; van Keulen, Hilde M.; Otten, Wilma; Kasteleyn, Marise; Molema, Johanna J. W.; de Hoogh, Iris M.; Chavannes, Niels H.; Numans, Mattijs E.; Evers, Andrea W. M.; Pijl, Hanno (Frontiers in Endocrinology, 2018)
From a biological view, most of the processes involved in insulin resistance, which drives the pathobiology of type 2 diabetes, are reversible. This theoretically makes the disease reversible and curable by changing dietary habits and physical activity, particularly when adopted early in the disease process. Yet, this is not fully implemented and exploited in healthcare due to numerous obstacles. This paper reviews the state of the art in all areas involved in a diabetes cure-focused therapy and discusses the scientific and technological advancements that need to be integrated into a systems approach sustainable lifestyle-based healthcare system and economy. The implementation of lifestyle as cure necessitates personalized and sustained lifestyle adaptations, which can only be established by a systems approach, including all relevant aspects (personalized diagnosis and diet, physical activity and stress management, self-empowerment, motivation, participation and health literacy, all facilitated by blended care and e-health). Introduction of such a systems approach in type 2 diabetes therapy not only requires a concerted action of many stakeholders, but also a change in healthcare economy, with new winners and losers. A “call for action” is put forward to actually initiate this transition. The solution provided for type 2 diabetes is translatable to other lifestyle related disorders.